Complex systems for evaluation of public health interventions: a critical review. (November 2018) - Egan, Matt; McGill, Elizabeth; Penney, Tarra; Meier, Petra S; Savona, Natalie; de Vocht, Frank; Popay, Jennie; Cummins, Steven; Smith, Richard; White, Martin; Er, Vanessa; Petticrew, Mark
Abstract: Background: There has been a growth in interest in applying systems thinking to public health research, including greater consideration of the complex and changing nature of real-world environments where public health interventions take place. We aimed to assess how a systems approach could be applied in the context of public health evaluation. Methods: A critical review of the literature was conducted to identify contrasting examples of systems approaches for in-depth comparison and analysis. To inform our protocol and identify relevant studies we held consultations with international researchers with relevant expertise (n=32). We tracked citations from previous reviews and searched Scopus, Medline, and Web of Science from Jan 1, 2014, to Aug 6, 2017. We used search terms relating to systems and complexity, evaluation, and public health and its social determinants. For inclusion, studies must have self-identified as taking a complex systems informed approach; evaluated one or more interventions or changes in a public health relevant specialty; and have been published in English. Study selection, appraisal, and data extraction and analysis were conducted independently by at least two reviewers with regular meetings to discuss contrasting viewpoints. Findings: 67 studies were included in the analysis. Public health topics varied: the most common concerned obesity, education, tobacco, and transport. Evaluations were classified by the systems approach taken. Six approaches were identified: system dynamics modelling (n=27), agent-based modelling (5), network analysis (3), qualitative research with a systems perspective (17), group model building (4), and miscellaneous innovative approaches to bringing system perspectives to a range of more traditional evaluation methods (17). Some evaluations used more than one approach. These different approaches were used to address different research questions but there was also some cross-over between approaches and purpose. Interpretation: Although systems evaluations are sometimes portrayed as a novel development in public health research, numerous examples already exist. There is no single or dominant systems approach to public health evaluation. Rather than try to advocate a single approach, we believe continued innovation in this field is most helpful at this time. Funding: National Institute for Health Research School for Public Health Research.